2003
DOI: 10.1046/j.1525-1438.2003.13192.x
|View full text |Cite
|
Sign up to set email alerts
|

Can we rely on the size of the lymph node in determining nodal metastasis in ovarian carcinoma?

Abstract: This study endeavored to determine whether lymph node size is a reliable indicator in determining lymph node metastasis in common epithelial ovarian cancer. We reviewed pathologic sections of pelvic and para-aortic lymph nodes removed from 104 ovarian carcinoma patients who underwent either primary surgical staging or secondary surgery from January 1994 to July 2001. All sections of each individual node were measured in two dimensions. The different sizes of nodes were studied statistically to determine the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…These authors suggested that systematic lymphadenectomy should be performed, rather than lymph node sampling, to determine the therapeutic impact of lymph node resection in epithelial ovarian cancers. Determining nodal metastases by palpation at the time of surgery has been found to have significant limitations (Petru et al, 1994;Arango et al, 2000;Eisenkop and Spirtos, 2001;Tangjitgamol et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that systematic lymphadenectomy should be performed, rather than lymph node sampling, to determine the therapeutic impact of lymph node resection in epithelial ovarian cancers. Determining nodal metastases by palpation at the time of surgery has been found to have significant limitations (Petru et al, 1994;Arango et al, 2000;Eisenkop and Spirtos, 2001;Tangjitgamol et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is worth noting that a recent review on this topic did not take into account the prevalence of extra-abdominal positive nodes [11]. The same occurred in a recent paper reviewing nodal metastasis in ovarian cancer [12]. Conversely, Cormio and colleagues [5] reviewed 162 patients with epithelial ovarian carcinoma and reported five cases of extra-abdominal lymphatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a noninvasive method to recognize lymph node metastases with certainty does not exist. However, if CT shows the presence of lymph nodes with a short axis >10 mm, suspicion of metastasis should be raised [ 37 ] . Of note, retroperitoneal lymphadenopathies above the renal vessels and around the celiac axis (Fig.…”
Section: Ovarian Cancermentioning
confidence: 99%